Desenvolvimento e Validação de um Modelo Baseado em Redes de Petri de um Sistema de Manufatura Didático no Cenário da Indústria 4.0 - Amaral, Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The growing complexity of industrial environments, resulting from the fourth industrial revolution, marked by the high connectivity of industrial environments, requires that industries be increasingly dynamic and flexible. In this scenario, industrial systems have become increasingly dynamic, parallel and non-linear. Discrete Event Systems theory provides the arsenal of tools necessary to deal with these problems and, together with Petri Nets, enable the functional description and analysis of these systems. This work uses these tools to model a manufacturing system based on flexible didactic stations and simulate it in order to test and validate the main qualitative characteristics that guarantee the good functioning of these systems. As a result, it was possible to analyze the state of spaces of the developed system and discuss its characteristics and its high combinational factor. The characteristics of limitation, liveliness and reversibility of the networks were also analyzed, making it possible to discuss important aspects of the system's behavior that could lead to failures, such as the accumulation of resources or unwanted interruption of operation.

A crescente complexidade dos ambientes industriais, decorrentes da quarta revolução industrial, marcada pela alta conectividade das plantas industriais, exige que as indústrias sejam cada vez mais dinâmicas e flexíveis. Diante deste cenário, os sistemas industriais têm se tornado cada vez mais dinâmicos, paralelos e não lineares. A teoria de Sistemas a Eventos Discretos fornece o arsenal de ferramentas necessário para lidar com esses problemas. Uma das ferramentas são as Redes de Petri, as quais possibilitam a descrição funcional e a análise desses sistemas. Este trabalho utilizou Redes de Petri para modelar um sistema de manufatura constituído de estações didáticas da FESTO e simula-lo a fim de testar e validar as principais características que garantem o bom funcionamento desses tipos de sistemas. Como resultado foi possível analisar o estado de espaços do sistema desenvolvido e discutir suas características e seu alto fator combinacional. Também se analisou as características de limitação, vivacidade e reversibilidade das redes, possibilitando discutir aspectos importantes sobre os comportamentos do sistema que poderiam levar a falhas, como o acúmulo de recursos ou interrupção do funcionamento.
Development and Validation of a Petri Net-Based Model of a Didactic Manufacturing System in the Industry 4.0 Scenario
Acompanha relatório
Keywords: Mathematical models; Industrial development projects; Modelos matemáticos; Análise de redes; Projetos de desenvolvimento industrial